Effect of age and sex on the associations between potential modifiable risk factors and both type 2 diabetes and impaired fasting glycaemia among West African adults - Ayuba Issaka; Adrian J. Cameron; Yin Paradies; William K. Bosu; Yèssito Corine N. Houehanou; Jean B. Kiwallo; Chea S. Wesseh; Dismand S. Houinato; Diarra J. P. Nazoum; Christopher Stevenson (BMC, 2022)
Abstract Background Type 2 diabetes mellitus (T2DM) is becoming one of the leading causes of morbidity and mortality worldwide, including among Africans. Knowledge of the association between traditional risk factors and both diabetes and pre-diabetes, and whether these differ by age and sex, is important for designing targeted interventions. However, little is known about these associations for African populations. Methods The study used data from WHO STEPS surveys, comprising 15,520 participants (6,774 men and 8,746 women) aged 25-64 years, from 5 different West African countries, namely Burkina Faso (4,711), Benin (3,816), Mali (1,772), Liberia (2,594), and Ghana (2,662). T-test and chi-square tests were used to compare differences in the prevalence of traditional risk factors for both sexes. Multinomial logistic regression was conducted to ascertain the relative risks (RR) and 95% confidence intervals (CI) for both T2DM and impaired fasting glucose (IFG) relating to each risk factor, including obesity [defined by BMI, waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR)], high blood pressure (HBP), fruit and vegetable consumption, physical inactivity, alcohol consumption, and smoking. Models for each of these traditional risk factors and interactions with age and sex were fitted. Results Factors associated with T2DM and IFG were age, obesity [defined by BMI, WC, WHtR, and WHR], HBP, smoking, physical inactivity, and fruit and vegetable consumption (p < 0.05). Analysis of interaction effects showed few significant differences in associations between risk factors and T2DM according to age or sex. Significant interaction with age was observed for HBP*age and T2DM [RR; 1.20, 95% CI: (1.01, 1.42)) (p = 0.04)], WHtR*age and T2DM [RR; 1.23, 95% CI: (1.06, 1.44) (p = 0.007)] and WHR*age and IFG [RR: 0.79, 95% CI: (0.67, 0.94) (p = 0.006)]. Some interactions with age and sex were observed for the association of alcohol consumption and both IFG and T2DM, but no clear patterns were observed. Conclusion The study found that with very few exceptions, associations between traditional risk factors examined and both IFG and T2DM did not vary by age or sex among the West African population. Policies and public health intervention strategies for the prevention of T2DM and IFG should target adults of any age or sex in West Africa.